2012 President's Plenary International Psycho‐Oncology Society: future directions in psycho‐oncology. Issue 7 (5th July 2013) - Breitbart, W.; Bultz, B. D.; Dunn, J.; Grassi, L.; Watson, M.
Abstract The inaugural President's Plenary was held at the 2012 International Psycho‐oncology Society's World Congress in Brisbane to provide a platform for dissemination of important initiatives and achievements of interest to cancer professionals globally. The vision of the International Psycho‐oncology Society – clarified and defined in 2004 – is that all cancer patients and their families throughout the world should receive optimal psychosocial care at all stages of disease and survivorship. Recent initiatives have been driven by the need to see psychosocial care available as a seamless part of holistic multidisciplinary quality cancer care and life‐extending lifestyle changes promoted and supported through the expertise of behavioural and social scientists. In keeping with World Health Organization targets that there is 'no health without mental health', cancer health must include mental health. This is in line with the patients' declaration to 'See us – not our disease'. The aim is to ensure that within the next decade, psychosocial care is acknowledged as a vital part of the patient journey and accepted globally as good practice within cancer care. The President's Plenary session covered the need for the following: Behavioural and social scientists to be integral to the planned lifestyle changes that the United Nations agreed, at a high‐level meeting in 2011, to reduce world cancer incidence and morbidity over the next decade; An internationally agreed standard of quality cancer care that includes psychosocial care for patients and their families and carers; An endorsement to assess distress as the 6th vital sign; A declaration that mental health within cancer health is a human right; Psycho‐oncology professionals to integrate into a federation promoting better national and international outcomes; strength in numbers speaking with a unified voice. The aim is to encourage dialogue between all cancer professionals and patient representatives to progress these targets; everyone has a voice. Copyright © 2013 John Wiley & Sons, Ltd.